The Effects of Limb Elevation on Muscle Oxygen Saturation: A Near‐Infrared Spectroscopy Study in Humans. Issue 3 (7th August 2015) - Palanca, Ariel A.; Yang, Arthur; Bishop, Julius A.
Abstract: Background: Orthopaedic and rehabilitation physicians often instruct patients to elevate a traumatized or postoperative lower extremity. Elevation is thought to improve patient comfort, as well as decrease swelling, wound complications, and the risk of compartment syndrome. Elevating a limb with increased compartment pressures, however, has been shown to reduce perfusion pressure and contribute to tissue ischemia. This investigation aims to advance our understanding of the tissue effects of limb elevation using a healthy patient model. Objective: To quantify the effects of elevation, experimentally induced ischemia, and immobilization on muscle oxygen saturation in the human leg using near‐infrared spectroscopy (NIRS). Design: Experimental crossover study. Setting: Orthopaedic Surgery research laboratory, Stanford Hospitals & Clinics. Patients for Participation: Twenty‐six healthy volunteers. Methods: Using transcutaneous sensors, we measured muscle oxygen saturation of the anterior compartment of the left (control) leg at 0, 15, and 30 cm of elevation relative to the heart using NIRS. A standardized short leg splint and a thigh tourniquet inflated to 50 mmHg were then applied to the right (experimental) leg to simulate a traumatized state. NIRS measurements were then repeated, again at 0, 15, and 30 cm of elevation. Muscle oxygen saturation values at various degrees of elevation of the control and experimental limb were then compared and analyzed by the use of a crossover study design and mixed‐effects regression. Main Outcome Measurements: Muscle oxygen saturation at varying levels of elevation in both the (1) control leg and (2) experimental leg in a simulated traumatic state. Results: Male (18) males and female (8) patients between 22 and 62 years of age (mean 29.8 years) were enrolled. Mean regional muscle oxygen saturation (rSO2 ) of the control limbs at 0, 15 and, 30 cm of elevation were 74.2%, 72.5%, and 70.6%, respectively, whereas mean rSO2 of the experimental limbs were 66.3%, 65.0%, and 63.3%. A statistically significant decrease of rSO2 was observed (mean 7.65%) in the experimental limbs compared with the control limbs. As elevation increased, there was a statistically significant decrease in rSO2 of 0.12% per centimeter of elevation. Elevation did not decrease the rSO2 in the experimental limb to a greater degree than in the control limb. Conclusion: Increasing levels of elevation in a human limb results in progressively compromised muscle oxygen saturation as measured by NIR.